EFEKTIFITAS ICE BREAKING MENGGUNAKAN KUIS MATEMATIKA TERHADAP MINAT BELAJAR SISWA PEMBELAJARAN - Sholeh, Ach. Fairuz; Noviartati, Kurnia (Jurnal Pembelajaran Matematika, 2018)
Abstract: The objective of the study is to determine ice breaking effectiveness using mathematics quiz on students' interest in learning mathematics. The population of this study is eleventh grade students at one of the state vocational schools (SMKN) in Surabaya in the academic year of 2017/2018. The research sample is students of class XI Multimedia 2, consisting of 33 students. This is an experimental research with pre-experimental method using one-shot case study design. In collecting the data, the researchers use students’ learning interest questionnaires, observation, and interview. The data analysis technique is carried out quantitatively based on the calculation of students’ mathematics learning interest questionnaire scores. The results show that  is 3.45 and  is 2.04 in 0.05 significance level. Because the value of  ( ), then Ha is accepted.  So, it can be concluded that there is an influence of ice breaking using mathematics quiz on students’ learning interest. It means that the application of ice breaking uses mathematics quiz on students' learning interest is effective.Keywords: Ice Breaking, Mathematics Quiz, Learning Interest.